The Autoimmune Diseases - Mackay, Ian R.; Rose, Noel R. (Elsevier/Academic Press, 2014)
Since publication of the 4th Edition of The Autoimmune Diseases in 2006, the understanding of the immune mechanisms underlying autoimmunity and autoimmune disease has significantly deepened and broadened. This fully revised 5th Edition incorporates new material and combines common themes underlying inductive and effector mechanisms and therapies that relate generally to the autoimmune disorders. It discusses the biological basis of disease at genetic, molecular, cellular, and epidemiologic levels and includes expanded coverage of autoinflammatory disease.- Resumé vydavatel
Keywords: autoimunitní nemoci; autoimmune diseases; elektronické knihy; sborníky; electronic books; papers of several authors